Nationalism by design the politics of dress in British Burma - Edwards, Penny
Colonial attempts to hem in racial and gender difference through practice, law and lore made dress a potent field of resistance in British Burma, giving rise to new strands of nationalism by design.
Keywords: p. Nationalism; Clothing and dress; British Burma